Molecular Identification of Symbiont Bacteria on Brown Alga Padina australis Hauck - Marina Flora Oktavine Singkoh; Sebrina Kuron; Stella Deiby Umboh; Deidy Yulius Katili; Beivy Kolondam; Agustina Tangapo (Postgraduate, University of Mataram, 2026)
The research aimed to identify the symbiont bacteria in brown alga Padina australis from the coastal waters of Molas, Manado city, Indonesia. Fresh samples were crushed with a mortar and pestle until smooth. A total of 1 g of the smooth alga was added into a test tube containing 9 mL of distilled water to obtain a 10-1 dilution. Next, 1 mL of a 10-1 solution was put into another test tube containing 9 mL of distilled water and vortexed for 15 minutes to obtain 10-2 dilution and so on until a 10-8 solution was obtained. 100 μL of solution from each series 10-4 – 10-8 was spread on NA media and incubated at a temperature of 27–29°C for 24 hours. DNA extraction was carried out following the modified Genomic DNA Mini Kit (Geneaid) protocol. DNA amplification was carried out using the 16S rRNA gene. Amplification using primers for the 16S rRNA gene BKXF (forward) and BKXR (reverse) resulted in fragments 1152 base pairs in length. The results of BLAST analysis of SK1 symbiont bacterial isolates found a Max score and total score of 1369, a query coverage of 97%, and a Percent Ident of 97.73%, which showed similarity to bacterial nucleotides of Bacillus cereus.